Antipsychotic-Related Movement Disorders: Drug-Induced Parkinsonism vs. Tardive Dyskinesia—Key Differences in Pathophysiology and Clinical Management - Ward, Kristen M. (Neurol Ther, 2018)
INTRODUCTION: Drug-induced parkinsonism (DIP) and tardive dyskinesia (TD) are stigmatizing movement disorders associated with exposure to dopamine receptor blocking agents such as antipsychotics, but they differ in their pathophysiology and clinical management. Treatment for one may worsen the other, and there are important diagnostic clues that assist in making an accurate assessment and instituting a rational treatment plan. METHODS: A literature review was executed to identify articles relating to the presentation, pathophysiology, epidemiology, and management of DIP and TD. RESULTS: DIP and TD prevalence estimates range from approximately 20 to 35% among antipsychotic users, but may be higher in select populations. DIP often presents as bradykinesia and rigidity, as well as rhythmic tremor, and the majority of cases appear within hours to weeks of initiation of therapy with an antipsychotic, or if dosage of the antipsychotic is increased. TD onset is delayed, typically appearing after at least 3 months or longer of treatment, and patients will commonly present with involuntary, abnormal facial movements such as lip smacking, puckering, chewing, or tongue protrusion. DIP often resolves with discontinuation of the causative agent, but TD may be permanent. Broadly, proposed mechanisms underlying these adverse events include decreased dopamine concentrations in the nigrostriatal pathway of the striatum and dopamine hypersensitivity, for DIP and TD, respectively. Pharmacologic treatment approaches for DIP have commonly included anticholinergic agents such as benztropine; however, anticholinergic medications can make TD worse. Switching the antipsychotic medication to one with lower propensity for DIP is an option for some patients. Amantadine, a non-anticholinergic agent used for the treatment of DIP, may be preferred in patients with comorbid DIP and TD. In TD, treatment options include the new reversible vesicular monoamine 2 transporter inhibitors, valbenazine and deutetrabenazine. CONCLUSIONS: It is important for clinicians to be able to recognize DIP and TD in patients using antipsychotics so that they can minimize the impact of these adverse events on their patients’ quality of life. Accurate diagnosis will drive the selection of the correct treatment. PLAIN LANGUAGE SUMMARY: Plain language summary available for this article.